2019
DOI: 10.24109/2176-6681.rbep.99i251.3337
|View full text |Cite
|
Sign up to set email alerts
|

Estudantes indígenas em universidades brasileiras: um estudo das políticas de acesso e permanência

Abstract: ResumoEste artigo aborda a presença indígena no ensino superior brasileiro baseado em pesquisa em universidade que executa política afirmativa para ingresso e permanência de estudantes indígenas. Analisa também teses e dissertações, distribuídas em diferentes programas de pós-graduação, que tematizam o ingresso de estudantes indígenas (implantação de políticas de acesso, processos seletivos para ingresso) e questões relacionadas à sua permanência na universidade (programas de apoio financeiro e pedagógico, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 0 publications
2
17
0
20
Order By: Relevance
“…All the difficulties reported by the study participants were similar to those reported in na-tional studies that evaluated the access and permanence policies of indigenous students from Brazilian universities 1,21,22 . Therefore, it can be observed that regardless of graduation, the challenges faced by indigenous students are common, resembling mainly economic, cultural and historical issues.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…All the difficulties reported by the study participants were similar to those reported in na-tional studies that evaluated the access and permanence policies of indigenous students from Brazilian universities 1,21,22 . Therefore, it can be observed that regardless of graduation, the challenges faced by indigenous students are common, resembling mainly economic, cultural and historical issues.…”
Section: Discussionsupporting
confidence: 70%
“…Another paradox observed in the narratives is that although HEIs have implemented affirmative actions for indigenous people, most of them do not have a planned policy of access and permanence that can lead to a good academic performance and provide a quality education. These factors, especially in the early stages, lead to higher dropout rates 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such observations have implications for our understanding of the difficulties facing affirmative action policies -one being that the permanence and academic progress of affirmative action students should be better investigated (see, for example, Bergamaschi et al, 2018;Cordeiro, 2010;Esta´cio and Almeida, 2016;Silva, 2016bSilva, , 2017 and another that the prejudices which these students face in their daily life at university need to be paid careful attention (Silva and Powell, 2016). Such studies have pointed out the need for universities to understand affirmative policies in their total complexity.…”
Section: Concluding Observationsmentioning
confidence: 99%